Мистика как культура и ее универсальные особенности - Жиртуева, Н.С. (Культура народов Причерноморья, 2013)
В статье рассматриваются феномены мистики и мистической культуры. Делается
вывод, что мистика является „единением” адепта с абсолютной реальностью, в результате чего
достигается познание Абсолюта и качественная трансформация психической жизни человека
(просветление, святость, пробуждение). Мистическая культура является совокупностью
теоретических положений и практических методов достижения «единения» адепта с Абсолютом.
Предлагается классификация универсальных особенностей мистической культуры. У статті розглядаються феномени містики та містичної культури. Робиться висновок, що
містика постає «єднанням» адепта з абсолютною реальністю, у результаті чого досягається пізнання
Абсолюту та якісна трансформація психічного життя людини (просвітлення, святість, пробудження).
Містична культура є сукупністю теоретичних положень та практичних методів досягнення «єднання»
адепта з Абсолютом. Пропонується класифікація універсальних особливостей містичної культури. The phenomena of mystics and mystic culture are examined in the article. The conclusion is drawn
that mystics is the “unity” of an adherent with the absolute reality; the cognition of the Absolute and the
qualitative transformation of psychical life of a man (enlightening, holiness, and awakening) are attained as a
result. A mystic culture is the totality of theoretical positions and practical methods of achievement of the
“unity” of an adherent with the Absolute. The classification of universal features of mystic culture is offered. 1.
There is an absolute spiritual reality, but the possibility to talk about the Absolute positively (negative or
apophatic theology) is denied. 2. A man belongs simultaneously to the world of the spiritual Absolute and to the
world of material (phenomenal) things what assists in formation of two forms of consciousness - egocentric and
enlightened. 3. Egocentric consciousness is the basic source of suffering of a man. 4. Suffering is the stimulus of
spiritual development of a man. 5. The primary purpose of a mystic is overcoming of egocentric consciousness
by means of a psychopractice. 6. The ultimate goal of a mystic practice is the “unity” with the Absolute and the
qualitative transformation of psychical life of a man. Mystic experience is transegocentric (“which overcomes
Ego”) and accompanied by the experience of mystic light.